Perinatal complications and live-birth outcomes following assisted reproductive technology: a retrospective cohort study - Lei, Ling-Ling (Chin Med J (Engl), 2019)
BACKGROUND: With the development of assisted reproductive technology (ART) and its increasing success rate in the mainland of China, more attention has been paid to the safety of ART. In this study, we explored the associations between conception by ART and pregnancy/perinatal complications, and neonatal outcomes compared with similar outcomes following spontaneous conception. METHODS: This retrospective cohort study of pregnancies over a 3-year period (2013–2015) was performed at Beijing Obstetrics and Gynecology Hospital, Beijing, China. Subjects were divided into two groups: conception by ART (n = 2256) or spontaneous conception (n = 6768). According to different fertilization modes, the ART group was divided into in vitro fertilization (IVF, n = 1873) and intracytoplasmic sperm injection (ICSI, n = 383) subgroups. The ART group was also divided into two different embryo transfer methods; fresh embryo transfer (ET, n = 1583) and frozen embryo transfer (FET, n = 673) subgroups. Pregnancy complications, perinatal complications, and neonatal outcomes of the enrolled subjects were investigated and analyzed by univariate analysis and multivariate logistic regression. RESULTS: After adjustment for maternal age, gravidity, parity, maternal education, smoking, alcohol consumption, and body mass index (BMI), pregnancies conceived by ART were associated with a significantly increased incidence of gestational diabetes mellitus (GDM; OR 1.88, 95% CI 1.56–2.27), gestational hypertension (OR 2.18, 95% CI 1.83–2.60), and intrahepatic cholestasis of pregnancy (ICP) (OR 2.79, 95% CI 2.15–3.64), compared with spontaneous conception. These associations were similar for the singleton group. In the twin group, only the incidence of ICP was significantly higher than in controls. We found that pregnancies conceived by ART were associated with perinatal complications, including placental abruption (OR 2.14, 95% CI 1.33–3.45), premature rupture of membranes (PROM; OR 1.24, 95% CI 1.06–1.45), postpartum hemorrhage (OR 2.89, 95% CI 2.33–3.59) and polyhydramnios (OR 2.01, 95% CI 1.29–3.16). The singleton group had a similar result with placental abruption, but not with fetal membranes ruptures before labor and polyhydramnios. There were no significant differences in the incidence of these perinatal complications in the twin group. Some neonatal outcomes, including preterm labor (OR 4.29, 95% CI 3.84–4.80) and low birth weight (OR 1.72, 95% CI 1.42–2.08), were more likely to occur with singleton births after ART. However, there were no significant differences for these outcomes from twin pregnancies. Perinatal complications and neonatal outcomes were consistent between the IVF and ICSI subgroups. The FET and ET subgroups showed a similar increase in complications, except for the incidence of placental abruption. After taking into account the effects of parity, birth plurality and maternal age, the ART group still exhibited increased maternal and neonatal complications, although some differences narrowed or disappeared. CONCLUSIONS: This retrospective cohort study demonstrated that patients who underwent ART were at increased risk of several adverse pregnancy outcomes compared with women who conceived spontaneously. These complications may be attributed in part to the relatively high multiple pregnancy rate after ART. Elective single embryo transfer should be promoted in China to reduce the obstetrical risks of ART pregnancy. Singletons of ART pregnancy exhibited increased maternal and neonatal complications as well, suggesting that underlying infertility or other maternal or parental factors may contribute to the adverse outcomes.